Revision of trapeziometacarpal arthroplasty: risk factors, procedures and outcomes - Mattila, Simo; Waris, Eero (Acta Orthopaedica, 2019)
Background and purpose — Revision surgery after trapeziometacarpal arthroplasty is sometimes required. Varying revision rates and outcomes have been reported in rather small patient series. Data on risk factors for revision surgery, on the final outcome of revision, and possible factors affecting the outcome of revision are also limited. We evaluated these factors in 50 patients. Patients and methods — From 1,142 trapeziometacarpal arthroplasties performed during a 10-year period, 50 patients with 65 revision surgeries were retrospectively identified and invited to participate in a follow-up study involving subjective, objective, and radiologic evaluation. The revision rate, risk factors for revision, and factors affecting the outcome of revision were analyzed. Results — The revision rate was 5%. Scaphometacarpal impingement was the most common reason for revision surgery. Patient age ≤ 55 years was a risk factor with a revision rate of 9% in this age group, whereas an operation on both thumbs during the follow-up period was a negative risk factor for revision surgery. There was no difference in revision risk between ligament reconstruction and tendon interposition with or without a bone tunnel. 9 patients had multiple revision procedures and their final outcome did not differ significantly from patients revised only once. Most of the patients felt subjectively that they had benefited from revision surgery and the subjective outcome measures (QuickDash and pain VAS) and the Conolly score were in the same range as previously described for revision trapeziometacarpal arthroplasty. Interpretation — Age ≤ 55 years is a risk factor for revision surgery. The type of primary surgery does not affect the risk of revision surgery and multiple revision procedures do not result in worse outcomes than cases revised only once. Mechanical pain caused by contact between the metacarpal and scaphoid is the most common indication for revision surgery. In general, patients seem to benefit from revision surgery for trapeziometacarpal osteoarthritis.